The legality of wasiyyah wajibah in achieving maqasid al-shariah / Md. Habibur Rahman and Abu Talib Mohammad Monawer - Rahman, Md. Habibur; Mohammad Monawer, Abu Talib (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Wasiyyah wajibah is an obligatory will, prescribed in some jurisdictions for the sake of grandchildren whose father dies during the lifetime of their grandfather. Maqasid shariah refer to the underlying objectives of Islamic rulings, which are summarized as the protection of faith, life, lineage, intellect and wealth. They are further described as the wellbeing (maslahah) of humankind which is portrayed as achieving the benefit and repulsing the harm. This study intends to analyze the lawfulness of wasiyyah wajibah in the context of maqasid shariah. The study is qualitative, and a method of content analysis is used to conduct this study. Though wasiyyah is voluntary, this form of wasiyyah is made obligatory to ensure social solidarity for the deprived grandchildren and social equality in distributing the inheritance of their grandfather among his inheritors. The study concludes that the lawfulness of wasiyyah wajibah goes in line with maqasid shariah as it protects the lives of underprivileged grandchildren and repulses the hardship of poverty and economic discrimination from their life. Thus, it ensures the wellbeing of those deprived grandchildren in particular and achieves social justice and social solidarity in Islamic inheritance at large.